GenTreat: pipeline computacional para montagem híbrida de genomas procarióticos - SANTOS, Victória Cardoso dos (2024)
The development of omics sciences has been greatly influenced by sequencing technologies. However, the large volume of data generated by these technologies necessitates the development of new computational tools for processing and analysis, particularly in genome assembly. Two main approaches are commonly used for assembly: reference-based assembly, which maps sequencing reads against a reference genome, and de novo assembly, which performs assembly without a reference. De novo assembly techniques include Overlap Layout-consensus, De Bruijn graph, and greedy algorithms. Although numerous tools have been developed over the years, challenges persist, including fragmented assembly results and redundant contigs. As a result, new methods have emerged, such as hybrid assembly strategies that combine results from different assemblers. However, existing tools utilizing this strategy often involve extensive and complex command lines. GenTreat is a computational pipeline with an intuitive graphical interface, was developed for automated hybrid assembly of prokaryotic genomes, performs assembly using two assemblers, merges the results, and then orders and annotates the assembled genome. Validation using raw reads from 61 organisms demonstrated that is a viable alternative for automated hybrid assembly, eliminating the need for using extensive command lines. The tool is available at: https://sourceforge.net/projects/gentreat/.